The 100th anniversary of the Poltava Gravimetric Observatory: past and present - Lubkov, M.V.; Pavlyk, V.G.; Halyavina, L.Ya.; Vachishyn, R.V.; Tyshuk, M.F. (S. Subbotin Institute of Geophysics of the NAS of Ukraine, 2026)
To the centenary of the Poltava Gravimetric Observatory of the S.I. Subbotin Institute of Geophysics of the NAS of Ukraine, an extended historical opus is presented on the expediency of the founding the scientific institution, its tasks, main stages of development, and main scientific achievements in the past and in our time. The observatory is one of the oldest scientific institutions of astronomical and geophysical specialization in Ukraine; on April 7, 2026 it celebrated its 100th anniversary. The observatory was created on the initiative of the outstanding astronomer and geophysicist academician O.Ya. Orlov, who headed it in 1926—1934 and 1938—1951. At the beginning, its main task was to conduct a survey and create a gravimetric map of Ukraine in order to realize its natural resource potential. This great work was successfully carried out by a relatively small team of employees of the Observatory in 1938. On the other hand, O.Ya. Orlov is rightfully considered one of the founders of modern geodynamics. Being a scientist of high erudition in the fields of astronomy, geodesy, geophysics, and seismology, O.Ya. Orlov consistently, especially during the Poltava period of his activity, introduced a comprehensive study of the Earth as a planet based on the methods of the specified disciplines. His innovative ideas and original methods were embodied and developed in the Observatory by the scientist himself and his outstanding students — E.P. Fedorov, Z.M. Aksentieva, M.A. Popov, and other scientists. The period 1938—1961 in the scientific activity of the observatory in the field of astronomic-geodynamic and geophysical research can be without exaggeration called an era of great achievements. At the current stage of the development of the Poltava Gravimetric Observatory, its main tasks are the continuation of fundamental and applied scientific research in the field of astronomy, geodynamics, geophysics, geotectonics, and oil and gas production in order to obtain new scientific knowledge and use it for scientific and practical purposes in the national economy of Ukraine.